2005
DOI: 10.1152/ajpendo.00125.2005
|View full text |Cite
|
Sign up to set email alerts
|

Leptin-mediated activation of human platelets: involvement of a leptin receptor and phosphodiesterase 3A-containing cellular signaling complex

Abstract: Elbatarny, Hisham S., and Donald H. Maurice. Leptin-mediated activation of human platelets: involvement of a leptin receptor and phosphodiesterase 3A-containing cellular signaling complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 35 publications
2
50
0
Order By: Relevance
“…Interactions between the N terminus of PDE4 and other proteins appear to be involved in the intracellular localization of these isoforms (37)(38)(39)(40), and previous studies have indicated that the N-terminal hydrophobic domains of PDE3 are involved in intracellular localization in transfected cells at least in part through interactions with other proteins (26,41). Several proteins that bind to PDE3 isoforms have been identified recently, but their role in the compartmentation of these enzymes remains unknown (42,43). Experiments designed to identify the mechanisms by which the N-terminal domains regulate the intracellular localization of these isoforms constitute an important direction for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between the N terminus of PDE4 and other proteins appear to be involved in the intracellular localization of these isoforms (37)(38)(39)(40), and previous studies have indicated that the N-terminal hydrophobic domains of PDE3 are involved in intracellular localization in transfected cells at least in part through interactions with other proteins (26,41). Several proteins that bind to PDE3 isoforms have been identified recently, but their role in the compartmentation of these enzymes remains unknown (42,43). Experiments designed to identify the mechanisms by which the N-terminal domains regulate the intracellular localization of these isoforms constitute an important direction for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-rich plasma (PRP) was prepared by centrifugation of heparinized (15 units/ml) blood (284 ϫ g, 15 min at 25°C) and used in aggregation studies as described in ref. 25. Platelets were washed in a Ca 2ϩ -free buffer (0.35% BSA, 137 mM NaCl, 2.7 mM KCl, 11.9 mM NaHCO3, 1 mM MgCl 2, 0.26 mM EGTA, 3 mg/ml apyrase ,and 5 mM Pipes, pH 6.5) and then in this buffer containing 2 mM CaCl 2 and 5 mM Hepes (pH7.4) before being loaded with Fluo-4 A.M. (3 M, 30 min) for use in Ca 2ϩ -release studies.…”
Section: Methodsmentioning
confidence: 99%
“…by guest www.bloodjournal.org From demonstrated. [12][13][14] Phosphorylated PDE3A has been reported by serine-threonine protein kinase Akt during leptin activation of platelets 15 and in mammalian oocyte maturation. 16 To investigate whether Akt might contribute to thrombin-induced phosphorylation/ activation of PDE3A, we used 3 pharmacologic inhibitors of candidate protein kinases: H89 (a PKA inhibitor), wortmannin (a PI3K inhibitor), and AktI (Akt inhibitor VIII).…”
Section: Thrombin Increases Pde3a Activity Via the Pi3k/akt Pathway Imentioning
confidence: 99%